Existence of a solitary planar bubble in symmetric channels. (August 2023) - Zhang, Fan
Abstract: Two-dimensional steady ideal fluids with gravity in finite height symmetric channels are considered. This model is well-known, but the existence results seem rare in the literature. For suitable incoming vertical velocity and the divergent nozzles, there exists a solitary bubble starting at the symmetric axis and extending downwards without limit. Finally, the inclination angle at the vertex of this bubble is investigated.